REGULATIONS AND ETHICS OF REPORTING ON PERSONS WITH DISABILITIES IN THE MEDIA: A COMPARATIVE STUDY OF INDONESIA AND INDIA - Setiana, Winda Ayu; Maifitri, Hafifah Maifitri; ’Aisyi, Tia Rahadatul; Tiara, Ayudya Soca; Shah, Rahul (Realism: Law Review, 2025)
Freedom of the press is a fundamental right in a democratic system guaranteed by Law Number 40 of 1999 concerning the Press. However, in some cases, freedom of the press can conflict with the rights of vulnerable groups, such as people with disabilities. This study focuses on a normative analysis related to the dilemma between freedom of the press and protection of the rights of people with disabilities, by referring to the laws and regulations in force in Indonesia. The results of the study indicate that although freedom of the press is guaranteed, there are regulations that govern the ethics of reporting so as not to violate the rights of people with disabilities, as regulated in Law Number 8 of 2016 and the Guidelines for Disability-Friendly Reporting from the Press Council. This study emphasizes the importance of a balance between freedom of the press and protection of the rights of people with disabilities in journalistic practice